A common image processing framework for 2D barcode reading - Ouaviani, E; Pavan, A; Bottazzi, M; Brunelli, E; Caselli, F; Guerrero, M (7th International Conference on Image Processing and its Applications, 1999)
The present work describes an image processing system able to locate, segment and decode the most common 2D symbol used in bar code applications. The different symbol are treated by exploiting their similarities, in order to achieve an unified computational structure.